Colonies initialization under laboratory conditions of Nyssomyia neivai and Migonemyia migonei (Psychodidae: Phlebotominae) in the north of Salta province, Argentina - Copa, Griselda Noemi (2019)
Leishmaniases are diseases transmitted via an insect vector, the sand fly (Psychodidae: Phlebotominae). In Oran (Salta, Argentina) Nyssomyia neivai is the most prevalent species followed by Migonemia migonei. These sand flies are medical relevance because they were found infected with Leishmania sp. in Argentina and Brazil. Establishing and maintaining of phlebotomine in colony is very important experimental study their biology, behavior and mutual relations with pathogens. The aim of our study was to study the life cycle of Ny. neivai and Mg. migonei under laboratory conditions and constructed a horizontal life table. Sand flies were captured in a peridomiciliary area of Orán city. The blood feeding females were captured on domestic animals and tree bark with mouth aspirators. A female with 5 males were maintained in rearing pots at 25 ± 2 ° C and 85-95% relative humidity. Larval food was a mixture of rabbit feces, fish feed, rabbit feed and adult sand flies food was sugar solution (30%). A total of 82 females were conditioned for oviposition of which 41.4% of female survived and oviposition (p=0.5076). Thirty-two were Ny. neivai and 2 Mg. migonei. The average number of eggs laid per female sand fly were 40.81 (Ny. neivai) and 59.50 (Mg. migonei). A total of 78 adults of Ny. neivai and 27 of Mg. migonei (p <0.001) emerged under laboratory conditions. The average time from egg to the emergence of the first adult was 37 days for Ny. neivai and 36 days for Mg. migonei. The proportions of the original surviving cohorts (lx) in each stage, for both species, were higher in the first stage (L1). The proportion of deaths per stage (dx) for Ny. neivai was higher in eggs and L1, while in Mg. migonei was in L2. The sand fly colonies could be initiated under laboratory conditions, which will allow the development of future vector and / or reservoir incrimination projects.